6 Risk-stratifying biomarkers to predict new onset HFpEF: potential roles for BNP, HS-troponin and galectin-3. (28th September 2016) - Watson, C; O'Connell, E; O'Reilly, J; Wilkinson, M; Gallagher, J; Ledwidge, M; McDonald, K
Abstract : Introduction: The future prediction of new onset heart failure with preserved ejection fraction (HFpEF) is an important component of disease prevention strategies. HFpEF is characterised by progressive onset of cardiac remodelling and ventricular dysfunction providing opportunities to detect these disease manifestations earlier and therefore enabling timely intervention. Based on HFpEF pathogenesis, potential biomarker candidates in the future prediction of new onset HFpEF include natriuretic peptides, high sensitivity Troponins, and galectin-3. The purpose of this study was to investigate the utility of these biomarker candidates in predicting new onset HFpEF in asymptomatic, event free patients with CVD risk-factors. Methods: The study population consisted of 90 patients selected from within the longitudinal STOP-HF study (Ireland) which comprises asymptomatic patients with CVD risk factors. Thirty of these patients developed HFpEF over time, and were propensity matched 2:1 by age and sex to a cohort that did not develop HFpEF (n = 60) over a similar time period. BNP, hsTroponin I, and galectin-3 were quantified in all patients at two time points. Median time between measurements was 1.2 years, and median time between follow-up measurement and future HFpEF event was 1.6 years. Results: Biomarker analysis of hsTroponin I and BNP at baseline and follow-up were statistically significant predictors of future new onset HFpEF, whereas galectin-3 at follow-up only was a significant predictor. A logistic regression model indicated that unadjusted biomarker combinations could significantly predict future HFpEF using both baseline (AUC 0.77 [0.68, 0.87]) and follow-up data (AUC 0.86 [0.79, 0.94]). NRI between adjusted models indicate that it is not necessary to take account of patient medications at 80% sensitivity. A simple clinical prediction rule to approximate the probability of future HFpEF development within the next 1–2 years was developed. Low and high risk was determined using BNP and galectin-3, with hsTropinin I being required to differentiate the intermediates. Applying this rule to the follow-up dataset yields sensitivity and specificity values of 83% and 71%, respectively. Discussion: We provided evidence for the utility of BNP, hsTroponin I, and Galectin-3 in the prediction of future HFpEF in asymptomatic event-free populations with CVD risk-factors. Validation of our biomarker combination models and clinical prediction rule in an independent population is required.